A novel approach for managing the incisions of tibial plateau fractures with soft tissue swelling - Yang Zhang; Yangyang Zhao; Shuanggong Liu; Zihan Yao; Zikang Jin; Wanli Ma (Scientific Reports)
Abstract To investigate the feasibility and clinical efficacy of a novel approach to managing the incisions used to treat tibial plateau fractures (TPFs) with soft tissue swelling. We retrospectively enrolled 64 patients with TPFs who underwent surgery at the Second Hospital of Shandong University. Patients were divided into two groups: Group A (n = 32) underwent early surgery with the novel incision management technique, and Group B (n = 32) underwent conventional surgery after swelling reduction. The perioperative data of the two groups were compared, including the time from injury to surgery, one-stage operation time, intraoperative blood loss, number of dressing changes, wound healing time, and hospitalization time. Preoperative and postoperative complications were assessed in both groups, and pain condition, degree of arthritis, limb function, imaging results, and quality of life were evaluated using validated scales. The time from injury to surgery, number of dressing changes, and hospitalization time in Group A were significantly lower than those in Group B (P < 0.05). There were no significant differences in one-stage operation time, intraoperative blood loss, or wound healing time between the two groups (P > 0.05). There were fewer preoperative and postoperative complications in Group A than in Group B (P < 0.05). The VAS and WOMAC scores were reduced in both groups (P < 0.05); Group A had lower VAS scores two weeks after surgery. There was no statistically significant difference in the WOMAC score between the groups. The modified Rasmussen functional and radiological scores were elevated in both groups (P < 0.05). There was no statistically significant difference between the two groups for the modified Rasmussen functional or radiological score at any of the time points (P > 0.05). In addition, the two groups did not differ in quality of life (P > 0.05). For patients with tibial plateau fractures without congestive blisters, open reduction and internal fixation at the early stage of swelling and wide-spacing interrupted suture and negative pressure wound therapy (NPWT) closure of the wound could help obtain excellent to good functional outcomes with fewer complications. This novel incision management approach and concept expands the surgical indications for these fractures.